Statistical considerations and impact of the FDA draft guidance for assessing adhesion with transdermal delivery systems and topical patches for ANDAs. Issue 5 (3rd September 2019) - Sun, Wanjie; Grosser, Stella; Kim, Carol; Raney, Sam G.
ABSTRACT: Until 2016, a ratio of means (ROM) non-inferiority (NI) test was recommended in FDA product-specific guidances (PSGs) to evaluate adhesion performance for prospective generic transdermal delivery systems (TDS). However, the ROM NI test had low power for well-adhering TDS, which were becoming increasingly prevalent. Mathematical proof and simulation revealed that the low power wasn't because the non-normality of adhesion data violated the normality assumption of parametric methods; it was because the ROM NI test was coupled with an adhesion scale where scores approached 0 as adhesion got better. In June 2016, FDA published a draft general guidance on TDS adhesion and recommended a new statistical approach, replacing the ROM NI test with a difference-of-means (DOM) NI test, using the same scale and primary endpoint (mean adhesion scores). An analysis of 40 TDS adhesion studies submitted in ANDAs after the publication of the 2016 draft guidance suggests that, consistent with simulation results, the new statistical approach markedly improves the low power, and thereby reduces the sample size required by the old approach for moderately to well-adhering TDS, while retaining comparable power for poorly adhering TDS. The new statistical approach thus enhances the potential approvability and patient access to well-adhering generic TDS.